A digital ecosystem for ICT educators, ICT industry and ICT students - Chin, Kum; Chang, Elizabeth; Atkinson, Douglas (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Worldwide ICT education (Information Communication Technology) is facing a major challenge of declining student enrolments; battling to keep its curriculum relevant and up-to-date while trying to meet the high demand of ICT skilled workers in domain, such as resources, health, government and commerce. This paper, documenting research in progress, discusses these issues and challenges in ICT education and proposes a solution in the form of a digital ecosystem in ICT education involving three main stakeholders: academics, students and the IT industry, and how they could come together to tackle the problems faced.